Atomistic Origins of Ductility Enhancement in Metal Oxide Coated Silicon Nanowires for Li‐Ion Battery Anodes. Issue 23 (16th October 2017) - Gao, Anthony; Mukherjee, Sankha; Srivastava, Ijya; Daly, Matthew; Singh, Chandra Veer
Abstract: Silicon nanowires (SiNWs) are a promising anode material for Li‐ion batteries due to their exceptionally high charge capacity. However, direct implementation is hindered by large volume expansion induced during lithiation, which results in mechanical failure during repeated charge cycling. Recent experimental works show thin metal oxide coatings can significantly increase the cycle stability of SiNWs. However, the deformation mechanisms underpinning this performance enhancement are not understood, presenting an opportunity for a fundamental investigation of core–shell mechanics. In this study, molecular dynamics simulations investigating the mechanical behavior of silica‐ and alumina‐coated SiNWs under uniaxial tension are performed. Metal oxide coated nanowires possess significantly improved ductility, increasing the elongation to failure from 16% to greater than 47%. This occurs without significant reduction in tensile strength, resulting in apparent toughness 2–4 times that of uncoated nanowires. During loading, the oxide coating absorbs strain energy through breaking of bonds between highly coordinated atoms. At the same time, the coating maintains the structural integrity of the silicon core by increasing the defect nucleation rate from the core‐coating interface, preventing localized deformation. Under both athermal (0 K) and room temperature conditions, the underlying deformation mechanism changes from amorphization within a localized shear band to dislocation twinning and large‐scale amorphization. Abstract : Molecular dynamics simulations of silica‐ and alumina‐coated silicon nanowires under uniaxial tension reveal atomistic origins for mechanical property enhancement in coated nanowires. Uncoated nanowires fail by amorphization within a localized shear band, while coated undergo dislocation twinning and large‐scale amorphization, improving ductility without significant reduction in tensile strength, increasing apparent toughness by 2–4 times.